Effect of saline sedimentary environment on pore throats of shale - Zhao, Z. X.; Wu, S. B.; He, M. W.; Fan, Y. J. (Frontiers in Earth Science, 2022)
Shale pore throat is one of the key factors affecting shale oil and gas exploitation. In order to study the effect of saline on shale pore throat in the continental lacustrine basin, the paleo-salinity of the lacustrine basin was analyzed using the Couth and Sr/Ba methods, and the pore throat characteristics of shale were observed by thin section and scanning electron microscope. The saline stage is divided into five stages: freshwater (0.5‰–1‰), brackish water (1‰–5‰), brackish water (5‰–15‰), brackish water (15‰–30‰), and high saltwater (>30‰). Shale is mainly reserved in micropores (organic, intercrystalline, and intergranular pores) and microcracks (along-layer, high pressure, structural, and mineral shrinkage cracks). Paleosalinity affects the pore throat characteristics of shale by controlling the mineral composition, rock combination type, and texture. Carbonate minerals tend to dissolve and form dissolution pores, resulting in pore throat enlargement and better physical properties. When salinity is low, the content of carbonate minerals increases with the increase in salinity. However, in the case of high salinity, the content of carbonate minerals gradually decreases, but that of sulfate and gypsum increases with the increase in salinity. The texture is conducive to the development of microcracks. With the increase in salinity, the number of textures first increases and then decreases. When the content is 15 ‰–30‰, there are most abundant textures, making it most likely to form microcracks. The results of this study play an important role in promoting the study of shale in the continental lacustrine basin.